Innovative impact indicators for university-industry collaboration - Barriga Ortiz, Pablo Andres (Acta Herediana, 2026)
University-Industry Collaboration (UIC) is increasingly vital for innovation, yet its success is often measured by narrow, traditional metrics like patent counts and licensing income. This approach fails to capture the full spectrum of value generated, including process efficiencies, human capital development, and broader societal benefits. This paper addresses this gap by proposing a holistic, multi-dimensional framework of innovative impact indicators. Synthesizing key findings from systematic literature reviews, the paper structures indicators into three critical domains: Input Indicators that measure the potential for success, Process Indicators that assess the health and management of collaboration, and Output and Impact Indicators that evaluate the full range of economic, institutional, and socio-environmental outcomes. The framework is grounded in the practical need for better measurement tools, as highlighted by feedback from international funding programs. It offers a practical and robust tool for universities, industry partners, and policymakers to more accurately evaluate and enhance the true value of their collaborative ventures.